Describing Phosphorus Sorption Processes on Volcanic Soil in the Presence of Copper or Silver Engineered Nanoparticles - Arancibia-Miranda, N; Arancibia-Miranda, N (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Engineered nanoparticles (ENPs) present in consumer products are being released into the agricultural systems. There is little information about the direct effect of ENPs on phosphorus (P) availability, which is an essential nutrient for crop growth naturally occurring in agricultural soils. The present study examined the effect of 1, 3, and 5% doses of Cu0 or Ag0 ENPs stabilized with L‐ ascorbic acid (suspension pH 2–3) on P ad‐ and desorption in an agricultural Andisol with total organic matter (T‐OM) and with partial removal of organic matter (R‐OM) by performing batch experiments. Our results showed that the adsorption kinetics data of H2PO4− on T‐OM and R‐OM soil samples with and without ENPs were adequately described by the pseudo‐second‐order (PSO) and Elovich models. The adsorption isotherm data of H2PO4− from T‐OM and R‐OM soil samples following ENPs addition were better fitted by the Langmuir model than the Freundlich model. When the Cu0 or Ag0 ENPs doses were increased, the pH value decreased and H2PO4− adsorption increased on T‐OM and R‐OM. The H2PO4− desorption (%) was lower with Cu0 ENPs than Ag0 ENPs. Overall, the incorporation of ENPs into Andisols generated an increase in P retention, which may affect agricultural crop production. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.